Ex-post adjustment for measurement error in child stunting calculations: An illustration from Egypt - Figueroa, Jose Luis; Kurdi, Sikandra (International Food Policy Research Institute, 2019)
This study provides estimated ranges for the magnitude of bias caused by measurement error in stunting rates in young children, a widely used proxy for long-term nutritional status.